On Methodological Questions in the Investigation of the Genesis of Religion - Černienė, Bronislava (Problemos, 1976)
The dialectic method requires to review the genesis of religion within the system of spiritual culture of the primeval epoch. The formation of the conception of primitive spiritual life in the history of religion was greatly influenced by the enlightenment and idealistic methodologies. The ideas of the latter, however, were overcome by the Marxist philosophy which has revealed the objective basis of spiritual production. The primitive syncretic spiritual life gave birth to different unrelated tendencies (cognition, religion, art) the development of which was determined by various needs of practical and industrial activities and many-sided interaction between the primitive society and reality. The studies of the genesis of religion as an element of the structured primitive spiritual life results in the final realization of the scientific Marxist method demanding to explain the origin of religion not by the peculiarities of human consciousness but by the objective conditions of human social existence.